2019
DOI: 10.1158/1541-7786.mcr-19-0181
|View full text |Cite
|
Sign up to set email alerts
|

CDX1 Expression Induced by CagA-ExpressingHelicobacter pyloriPromotes Gastric Tumorigenesis

Abstract: Intestinal-type gastric cancer often results from Helicobacter pylori infection through intestinal metaplasia, a transdifferentiated premalignant phenotype. Because H. pylori virulence factor CagA has been associated with aberrant expression of the transcription factor CDX1, which regulates intestinal differentiation, we explored its relationship with H. pylori infection and function during gastric carcinogenesis in normal gastric epithelial cells and gastric cancer cell lines. Infection of HFE 145 cells with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 46 publications
0
20
0
1
Order By: Relevance
“…In addition to the type of EPIYA-motifs, strains with amino acid polymorphism within the Western-specific EPIYA-B motif like EPIYT-B may influence CagA activity, reducing the ability to induce hummingbird phenomena and IL-8 expression conferring lower risk for gastric cancer and a higher risk for duodenal ulcer development [159]. A recent study demonstrated that secreted H. pylori CagA can induce caudal type homeobox 1 (CDX1) expression, which is a homeobox transcription factor that plays an important role in human intestine development and maintenance [160,161]. CDX1 activation promotes cell proliferation, invasion/migration, intestinalization of gastric epithelial cells, and stem cell-like phenotype induction leading to cancer development and failure of common gastric cancer chemotherapies [160].…”
Section: Virulence Factors Associated With Gastric Epithelial Cellmentioning
confidence: 99%
“…In addition to the type of EPIYA-motifs, strains with amino acid polymorphism within the Western-specific EPIYA-B motif like EPIYT-B may influence CagA activity, reducing the ability to induce hummingbird phenomena and IL-8 expression conferring lower risk for gastric cancer and a higher risk for duodenal ulcer development [159]. A recent study demonstrated that secreted H. pylori CagA can induce caudal type homeobox 1 (CDX1) expression, which is a homeobox transcription factor that plays an important role in human intestine development and maintenance [160,161]. CDX1 activation promotes cell proliferation, invasion/migration, intestinalization of gastric epithelial cells, and stem cell-like phenotype induction leading to cancer development and failure of common gastric cancer chemotherapies [160].…”
Section: Virulence Factors Associated With Gastric Epithelial Cellmentioning
confidence: 99%
“…47 In vitro, the expression level of CDX2 increased in GC cell lines infected by H. pylori, and abnormal expression of CDX1 was induced by infection with CagA-positive H. pylori strains. 49,50 In addition, some studies indicated that the CDX2 expression level will decrease after H. pylori eradication prior to the development of GIM. 51,52 However, a prospective study showed that H. pylori eradication had no significant effect on GIM development.…”
Section: Roles Of Cdxs In H Pylori-induced Gimmentioning
confidence: 99%
“…Accumulation of intracellular CagA was confirmed in CD44+ gastric CSCs [138]. H. pylori-infected (CagA-positive) gastric cancer cells exhibit CSC properties via increased expression of surface markers-CD44 and Lgr5 with Nanog, Oct4, and c-myc upregulation [139,140]. CagA impairs transcription factor CDX1 expression, promoting EMT, and CSC features in gastric epithelial cells [141].…”
Section: Introductionmentioning
confidence: 96%